2022
DOI: 10.33448/rsd-v11i12.34353
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de estudantes universitários da área da saúde com relação à utilização de medicamentos e a prática da automedicação

Abstract: A prática da automedicação é um comportamento comum em diversos grupos populacionais, inclusive entre os estudantes universitários. Neste contexto, o objetivo deste estudo foi verificar o comportamento de estudantes universitários da área da saúde com relação à utilização de medicamentos, particularmente, à prática da automedicação. Trata-se de um estudo epidemiológico descritivo, observacional, transversal realizado através da avaliação da prática da automedicação entre universitários. Foram utilizados questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Despite some limitations inherent to the design of the present study, as the analysis is based on the self-reported responses, our findings corroborate the literature, evidencing the need for professional support for students due to their extensive academic curriculum and pressures, which serve as a trigger for mental disorders such as anxiety, depression, and psychoactive substance abuse. It should be noted that some students have attempted inappropriate self-medication that put their health in hazard; a plausible explanation for this phenomenon is that they have incomplete knowledge about medical practice and limited experience, but the same justification cannot be applied to the already trained and qualified professionals, who have attempted self-medication and face the same problems [20][21][22]. This survey also highlighted the lack of information regarding the adverse effects caused by self-medication.…”
Section: Discussionmentioning
confidence: 96%
“…Despite some limitations inherent to the design of the present study, as the analysis is based on the self-reported responses, our findings corroborate the literature, evidencing the need for professional support for students due to their extensive academic curriculum and pressures, which serve as a trigger for mental disorders such as anxiety, depression, and psychoactive substance abuse. It should be noted that some students have attempted inappropriate self-medication that put their health in hazard; a plausible explanation for this phenomenon is that they have incomplete knowledge about medical practice and limited experience, but the same justification cannot be applied to the already trained and qualified professionals, who have attempted self-medication and face the same problems [20][21][22]. This survey also highlighted the lack of information regarding the adverse effects caused by self-medication.…”
Section: Discussionmentioning
confidence: 96%
“…De acordo com Santos e colaboradores (2022), os medicamentos mais utilizados por estudantes são os antigripais, analgésicos e antiácidos, e em mais da metade dos casos, a utilização ocorre por automedicação 17 . Os analgésicos estão entre os mais utilizados de acordo com o observado por Valério e Morretes (2020), justamente pelas vantagens destes em promover um alívio da dor, serem de fácil aquisição e por apresentarem venda livre, sem necessidade de receita médica.…”
Section: Os Universitários Brasileiros E O Uso De Medicamentosunclassified